Primary Leiomyosarcoma of Bone: Analysis of Prognosis. (11th March 2012) - Brewer, P.; Sumathi, V.; Grimer, R. J.; Carter, S. R.; Tillman, R. M.; Abudu, A.; Jeys, L.
Abstract : Leiomyosarcoma of bone is just one of the variants of spindle cell sarcoma of bone characterised by the expression of desmin and other markers indicating a significant element of smooth muscle in the tumour, without osteoid production we have investigated the management and outcome of this rare type of primary malignant bone tumour. Method . Retrospective review of data stored on a prospective database. Results . In a database of 3364 patients with primary malignant bone sarcomas, 31 patients were identified with a primary leiomyosarcoma of bone. There were 12 males and 19 females with a mean age of 46 and tumour size of 8 cm. The most common site was the distal femur followed by the proximal tibia. Treatment was with chemotherapy and surgical resection. Seven of the patients had metastases at diagnosis. Surgery was carried out in 28 patients, 8 having amputation and 20 limb salvage. Three patients developed local recurrence, but half developed metastases. All patient disease-specific survival was 57% at five years and 44% at 10 yrs but for those without metastases was 82% and 60%, respectively. The only prognostic factors were metastases at diagnosis. Conclusion . Leiomyosarcoma of bone is a very rare primary malignant bone tumour affecting a predominantly older population. Despite the high incidence of metastases, survival is better than for other bone sarcomas for those without metastases at diagnosis.